PEMBELAJARAN SEJARAH DALAM MENGEMBANGKAN NILAI KARAKTER DI SMKN 46 JAKARTA - Sigit Widya Pratama; Desvian Bandarsyah (Prosiding Seminar Nasional Berseri, 2020)
This study aims to determine the history of learning in developing character values at SMKN 46 Jakarta. This research uses a qualitative approach. The results of the study show that: (1) Integration of character values in history learning is carried out by the teacher starting from the process of planning, implementation, and evaluation in which the inculcation of character values has been integrated into the RPP and syllabus which is instilled in students when the learning process takes place which is integrated with character values. (2) The manifestation of character values in the history of learning is manifested in the attitudes of students whose behavior is aimed so that students can later become better outside of school, in the community, as well as in the family and work environment. Thus it can be concluded that history learning in developing the character values of students in SMKN 46 Jakarta has been carried out in school activities and history learning activities in class.